Livelihood Security Index Assessment among Millet Farmers in North Eastern Hill (NEH) States of India - Sangappa,; Rafi, D.; Candhini, K.; Charishma, E.; Meghana, G. (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted from August, 2022 to August, 2023 in the North Eastern Hill (NEH) areas of Arunachal Pradesh, Tripura, and Meghalaya as part of the ICAR-IIMR, Hyderabad institutional project. Ex-post facto research design was used for assessing the livelihood security of millet farmers in tribal areas. The study constituted to 6 districts in 6 blocks and 24 villages with a sample of 240. Livelihood security index values were used to find the livelihood security of tribal farmers. According to the research findings, various components of livelihood security viz., social, food and nutritional, institutional, ecological, infrastructural, and economic aspects were assessed. Results indicated that economic security (0.85), food and nutrition security (0.84), infrastructural security (0.81), and ecological security (0.77) have received higher livelihood index values. The higher value of the livelihood index stated that significant improvements were observed in the livelihoods of tribal farmers through the technological implementations of IIMR with the support of central and state agricultural universities in the study area. The study revealed that social security was recorded as low. The study also highlighted that there is a strong need to improve the social status of millet farmers in NEH areas after post-project implementation. Achieving social security requires time and it can be improved through greater community engagement by the farmers, capacity-building initiatives, and advanced technical support for stimulating the social standards of NEH areas.